2011
DOI: 10.1525/mp.2012.29.3.269
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Formal Structure in Liking for Popular Music

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Some of the individual verses and choruses, however, were less discernable to listeners of contemporary music. These findings are in line with an earlier study, in which we asked listeners to place each of the sections of contemporary songs separately on a timeline (Rolison & Edworthy, 2012). The present findings indicate that listeners are sensitive to the overall formal structure of a song determined by the ordering of its sections.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Some of the individual verses and choruses, however, were less discernable to listeners of contemporary music. These findings are in line with an earlier study, in which we asked listeners to place each of the sections of contemporary songs separately on a timeline (Rolison & Edworthy, 2012). The present findings indicate that listeners are sensitive to the overall formal structure of a song determined by the ordering of its sections.…”
Section: Resultssupporting
confidence: 92%
“…Although the verses and choruses often alternate in popular music, in some songs choruses follow verses, and in others verses instead follow choruses (e.g., "Ain't no sunshine" by Bill Withers, "She loves you" by the Beatles). Rolison and Edworthy (2012) used a similar procedure to the one used by Deliège et al (1996) to explore listeners' sensitivity to the formal structure of popular contemporary songs. In the Rolison and Edworthy (2012) study, musically untrained participants were asked to locate the sections of unfamiliar songs on a timeline from the beginning to the end of the song.…”
mentioning
confidence: 99%
“…Over the last 30 years, multiple studies have explored the perception of musical form in tonal music. Most have suggested that local cues (small scale and short duration) may take priority over global relationships (large scale and overall formal structure) in the perception of musical information (Deliège et al, 1996;Tillmann and Bigand, 2004;Rolison and Edworthy, 2012). Moreover, studies which have examined the impact of rearranging segments of music on the listener have found that the participants may not be able to differentiate between the original and the rearranged pieces of music (Tillmann and Bigand, 1996) and that the listeners may not prefer an original over an arrangement (Eitan and Granot, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These issues may account for the failure of listeners to distinguish modified and original musical structures; the resulting differences in coherence may be too subtle to give a large enough effect for the samples sizes used. Similar problems can also be found in the application of this paradigm to the perception of song form in popular music (Rolison & Edworthy, 2012).…”
Section: Large-scale Thematic Structurementioning
confidence: 72%